A modified foam drainage test protocol for assessing incompatibility of admixture combinations and stability of air structure in cementitious systems. (30th June 2019) - Wang, Xin; Wang, Xuhao; Sadati, Seyedhamed; Taylor, Peter; Wang, Kejin
Highlights: The effects of testing temperature, procedures, and admixture dosages on stability of generated foam was assessed. Modified foam drainage method to evaluate the compatibility between air entraining agent, water reducing agent, and cement. A pass/fill limit was proposed for foam drainage method. Found a good correlation between results from modified foam drainage test and air void system stability in concrete mixtures. Abstract: Unexpected interactions between chemical admixtures and other ingredients in a cementitious systems may occur as cementitious systems become more complex and demands on the systems are more rigorous. Incidents related to use of chemical admixtures in highway concrete have been reported in some states. A common problem was instability of the air void system with air contents changing significantly during handling and placing. The stability of an entrained air void system in fresh concrete can have a profound influence on the potential durability such as freeze/thaw resistance. A technique known as the foam drainage test has been in use to assess the potential stability of air void system in fresh paste samples in the laboratory. However, there has been little reported work on the correlation between the test results and air void system in hardened concrete. In addition, the method, as published, is not rigorous with respect to some factors such as test temperature, and there is no pass/fail limit to evaluate testing results. The work presented here sought to evaluate the effects of variables such as environmental conditions, testing procedures, and admixture dosages on the data obtained. Multiple cementitious combinations with various chemical admixtures, such as air entraining and water reducing agents, were used to propose a pass/fail limit for admixture combinations. In addition, selected combinations were used to prepare concrete specimens and the air void system was evaluated after handling activities were mimicked in the lab.